Faktor-Faktor Penentu Tingkat Kemiskinan Regional Di Indonesia - Samsubar Saleh (Universitas Islam Indonesia, 2002)
The purpose of this research is to analyze the determinants of regional variation in Indonesia poverty. This research uses cross-sectional and pooling data of the period 1996 and 1999. The empirical results show that the determinants of regional variation in Indonesia poverty are human development index (HDI) (includes: income percapita (YPC), life of expectacy (HH), and mean years of schooling /RS)), income inequality (RG), physical investment (IFP), population without access to health facilities (PNH), and population without access to save water (PNW), and economic crisis (DT).Keywords: kemiskinan, pooling data, cross-sectional data.